Pengaruh Partisipasi Masyarakat Terhadap Efektivitas Program Inovasi Desa Budi Daya Jamur Tiram Di Desa Jenetaesa Kecamatan Simbang Kabupaten Maros (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to determine and analyze the effect of community participation and its influence on the effectiveness of the Jenetaesa Village innovation program, Simbang District, Maros Regency. This study used a mixed method by using a type of survey research by observing using a questionnaire to collect data related to research variables. The population in this study were the community or family heads of the Jenetaesa Village, Simbang District, as many as 421 family heads in the Jenetaesa Village, Simbang District, Maros Regency. This study used simple random sampling technique or random sampling, with a total sample of 80 people. The results of this study showed that community participation had a positive and significant effect on the effectiveness of village innovation programs, with an Adjusted R Square coefficient of 0.636 meaning that 63% of community participation affected the effectiveness of village innovation programs in Jenetaesa Village, Simbang District, Maros Regency.